2017
DOI: 10.18632/oncotarget.21338
|View full text |Cite
|
Sign up to set email alerts
|

Targeting oral cancer stemness and chemoresistance by isoliquiritigenin-mediated GRP78 regulation

Abstract: Cancer stem cells (CSCs) are cells that drive tumorigenesis, contributing to metastasis and cancer recurrence as well as resistance to chemotherapy of oral squamous cell carcinomas (OSCC). Therefore, approaches to target CSCs become the subject of intense research for cancer therapy. In this study, we demonstrated that isoliquiritigenin, a chalcone-type flavonoid isolated from licorice root, exhibited more toxicity in oral cancer stem cells (OSCC-CSCs) compared to normal cells. Treatment of isoliquiritigenin n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 63 publications
0
28
0
Order By: Relevance
“…By means of the selective inhibition of GRP78 ATPase with isoliquiritigenin (a chalcone-type bioflavonoid), it was shown that the binding of GRP78 to β-catenin is necessary to realize the GRP78/β-catenin/ABCG2 pathway in breast CSCs, which contributes to their drug resistance [232]. Later, GRP78-downregulating treatments with isoliquiritigenin enabled Hu et al [233] to discover the essential role of GRP78 in the expression of CD44, ALDH1, and ABCG2 (all are stemness markers) and the ability for invasion and metastatic spread and resistance to chemotherapy in CSCs from oral squamous cell carcinomas. Silencing of GRP78 suppressed self-renewal and radioresistance of glioma CSCs, which was due to the increase in the microRNA-205 level [234].…”
Section: Intracellular Grp78mentioning
confidence: 99%
See 4 more Smart Citations
“…By means of the selective inhibition of GRP78 ATPase with isoliquiritigenin (a chalcone-type bioflavonoid), it was shown that the binding of GRP78 to β-catenin is necessary to realize the GRP78/β-catenin/ABCG2 pathway in breast CSCs, which contributes to their drug resistance [232]. Later, GRP78-downregulating treatments with isoliquiritigenin enabled Hu et al [233] to discover the essential role of GRP78 in the expression of CD44, ALDH1, and ABCG2 (all are stemness markers) and the ability for invasion and metastatic spread and resistance to chemotherapy in CSCs from oral squamous cell carcinomas. Silencing of GRP78 suppressed self-renewal and radioresistance of glioma CSCs, which was due to the increase in the microRNA-205 level [234].…”
Section: Intracellular Grp78mentioning
confidence: 99%
“…In another study dedicated to targeting GRP78 in glioblastoma CSCs, pterostilbene, a plant-derived stilbenoid and dietary component, impaired self-renewal and radioresistance in glioblastoma CSCs through modulating GRP78 signaling and the GRP78/miR-205 axis [234]. Another plant-derived compound, isoliquiritigenin (a chalcone-type bioflavonoid), was shown to suppress both the self-renewal ability and the expression of cancer stemness markers, such as CD44 and ALDH1, in CSCs from oral squamous cell carcinoma; in addition, the invasive and metastatic capacities became impaired in isoliquiritigenin-treated oral CSCs [233]. The anti-stemness effects of isoliquiritigenin were associated with the downregulation of GRP78 (both intracellular and membrane-bound GRP78), whereas those effects could be reversed by GRP78 overexpression [233].…”
Section: Targeting Intracellular Grp78mentioning
confidence: 99%
See 3 more Smart Citations